Facile fabrication of binary wettability patterned microstructure for microfluidics. (17th February 2021) - Tang, Biao; Wei, Miaoyang; Shao, Wan; Barman, Jitesh; Sun, Hailing; Lu, Longsheng; Groenewold, Jan; Wang, Yao; Zhou, Guofu
Abstract: Diverse wetting contrasts of binary wettability patterns in nature have inspired a versatile platform for microfluidics manipulation. To date, nevertheless, building a binary wettability patterned micro/nano structure with highly ordered configuration has inevitably brought wettability contamination challenges in interface control. Herein, this work studied a facile approach to fabricate permanent and contamination-free microstructure with high contrast wettability by means of adding a small amount of surfactant to the photoresist, rather than through any surface modification of the substrate. Accordingly, we focused on a systematic research of the wettability contamination prevention, binary wettability interfacial pattern control, and the dynamic electrowetting performance. The results demonstrated the proposed fabrication of binary wettability patterned microstructure without reactive-ion etching would be advantageous for contamination-free, permanent, simple, reliable and precise process, which could enable the microfluidic electrowetting display highly stable and controllable, thus it is expected to suit fields all the way from microfluidic-based fundamental studies to materials processing engineering and device applications.